Proceedings Second International Conference on Information Processing
The proceedings features several key-note addresses in the areas of advanced information processing tools. This area has been recognized to be one of the key five technologies poised to shape the modern society in the next decade. It aptly focuses on the tools and techniques for the development of Information Systems. Emphasis is on pattern recognition and image processing, software engineering, mobile ad hoc networks, security aspects in computer networks, signal processing and hardware synthesis, optimization techniques, data mining and information processing.